Artificial intelligence in test automation - Trudova, Anna; Buchalcevová, Alena, 1958-; Doležel, Michal; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2019)
Artificial intelligence (AI) has made a considerable impact on the software engineering field, and software testing is not an exception. AI techniques could help to achieve the highest possible level of software test automation. This master thesis is focusing on evaluating existing implementations of artificial intelligence in test automation, which corresponds with the main goal of the work. The main goal is to identify and evaluate how artificial intelligence could be used in software test automation; it is supported by several objectives: to introduce concepts of test automation and artificial intelligence, to identify value that artificial intelligence can bring into test automation, to develop and evaluate a methodology of using AI-based tool for mobile applications testing.The thesis is divided into two major parts. Chapters from one to three belong to the theoretical part of the thesis and are dedicated to the theoretical background on software test automation and artificial intelligence. The theoretical part of the thesis also includes a Systematic Literature Review on theme of artificial intelligence in software test automation and by that presents the current situation and interconnection of the mentioned fields.The second part of the thesis presents a new methodology design of using AI-based tool for mobile application testing. It provides concepts, activities, roles, tools, work products and guidance and fields of application of the methodology. The proposed methodology can be considered as the main contribution of this work. The last chapter is dedicated to practical application and evaluation of the methodology on a real-world mobile application. Overall outcome of evaluation is that the methodology is applicable to real world project and application.
Vedoucí práce: Alena Buchalcevová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: informační systémy a technologie [obor dipl. práce]; diplomové práce; master's theses